Fiscal decentralization and political centralization in China: implications for regional inequality - Zhang, Xiaobo (International Food Policy Research Institute, 2005)
While, politically speaking, China has a centralized government structure with strong top-down mandates, under the country’s current fiscal system, local governments are responsible for providing most local public goods and services. Large differences in economic structures and revenue bases exist, however, causing the implicit tax rate and fiscal burdens in support of local government functions to vary significantly across jurisdictions. Regions initially endowed with a broader nonfarm tax base do not need to rely heavily on new and existing firms to finance public goods provision, which creates a healthy investment environment in support of nonfarm sector growth. In contrast, local governments in regions where agriculture is the major economic activity spend the majority of their resources on their own operating costs, leaving little for public investment. Because of the relatively high transaction costs associated with collecting taxes from the agricultural sector, local governments tend to levy the existing nonfarm sector heavily, thereby greatly inhibiting its growth. As a result, regional differences in economic structures and fiscal dependent burdens may translate into widening gaps in equality.